Perancangan Aplikasi Peminjaman dan Pengembalian Buku Berbasis Web Pada Kantor Perpustakaan dan Arsip Daerah Provinsi Sumatera Utara - Khairani, Melvika; Purnamawati, Sri; Rani, Putri Meuthia; Firmansyah, Bayu Duta (Yayasan Pendidikan Al-Yasiriyah Bersaudara, 2024)
A library is a room managed by an educational institution, providing a variety of book collections. The purpose of this study is to develop a web-based application that can facilitate the process of borrowing and returning books at the provincial library of North Sumatra. The web-based book borrowing application at the Provincial Library and Archives of North Sumatra is used to facilitate the process of borrowing and returning books, as well as to help the people of North Sumatra in finding information and expanding their knowledge from the books available at the Provincial Library and Archives of North Sumatra through more advanced library services. The method used in the development of this system is the waterfall model (Software Development Life Cycle). This model uses a systematic and sequential approach, with phases such as requirements, design, implementation, verification, and maintenance. The results of this study show that the web-based book borrowing and returning application at the Provincial Library and Archives of North Sumatra can facilitate the process of borrowing and returning books, with features such as users being able to borrow and return books online, view a list of available books, and track the status of their book loans online.